DEVELOPMENT OF REPAIR KITS FOR KNOTS OF TRANSPORT EQUIPMENT AND TECHNOLOGICAL EQUIPMENT - Kushaliyev D.K.; Vinogradov A.N.; Baltayev T.A.; Ermanova B.A. (Scientific Journal of Pedagogy and Economics, 2020)
Sliding and rolling bearings are applied in transportation and production equipment, these bearings operate under high loads in reciprocating/rotary mode. They are used in railroad, road, and agricultural transport for suspensions, dampers, steering, shaft drives, in garment equipment, mining, oil and gas production and processing, as well as some other industries. However, their operation lifetime is insufficient and recovery of such couplings by conventional methods comprised of replacement with repair kits of similar design does not solve this problem. As assumed in this article, the operation lifetime of couplings operating under heavy loading in reciprocating/rotary mode can be increased by improved recovery of their operability using repair kits based on new operation principles of tribocouplings, that is, sliding bearings with movable spring bearing boxes. The design of repair kit design of rubber bushing in the form of sliding bearing with movable conical spring boxes has been theoretically substantiated. Mathematical models of size variations of movable conical spring box of sliding bearing of damper rubber bushing have been developed. Theoretical importance of the work is comprised of the expanded proven concepts of recovery of damper rubber bushings using repair kits with movable spring boxes. Practical significance is that the developed repair kits of damper rubber bushing are characterized by operation lifetime higher by 1.5…2 times in comparison with regular kits. The obtained results can be applied for development of new engineering solutions, for improvement of recovery of transportation and production equipment with couplings operating under high loads in reciprocating/rotary mode.